Argentine Foreign Policy: Action and Inaction in the Face of the War in Ukraine, 2019-2023 - Ceppi, Natalia (2025)
This article explores the dynamics of action and inaction by the Argentine government under Alberto Fernández (2019-2023) in response to the war in Ukraine. It examines both its political-diplomatic positioning and the energy dimension of its foreign policy. The study is situated within the subfield of foreign policy analysis and adopts a qualitative methodology based on bibliographic and documentary review. The findings reveal that the Fernández administration adopted ambivalent positions in the political-diplomatic sphere (action), while opting for inaction in response to the energy-related challenges stemming from the conflict. This duality reveals a lack of coherence and consistency in its foreign policy practice, largely attributable to the intermestic nature of Argentina’s external affairs.